Les espaces de discussion sur Internet comme dépassement des communautarismes ? Le cas de l’agora virtuelle libanaise. - Rawad Chaker (Éducation et Socialisation)
In our contemporary history, the debate about identities and communities has never been more important than it is today. This article looks at the issue of Internet discussion spaces and its effects on the nature of online interactions in a context marked by communitarianism. Could school teach citizenship through digital communication and information tools? In this paper, the light is shed on the effects of estrangement or community rapprochement that this kind of exchange allows us to observe. We wonder whether the virtual agora fits into a democratic public space’s paradigm, which would then position it in the wider public debate about the Internet, education and citizenship issues. We use the regime of the Civic City, taken from the Economies of Worth theory, as a methodological matrix in order to analyze online discussion material, taken from 6 Lebanese information websites, which typically belong to a context marked by political and community-based fragmentation.